Pengembangan Motorik Kasar Anak Usia Dini Melalui Permainan Gerakan Binatang - Nuridayu Nuridayu; Aminoh Kiya; Ida Windi Wahyuni (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2020)
Early childhood is the successor of the family that must be fostered and educated with various aspects of development. The child's gross motor includes all the muscular activities of the hands, feet, and all members of the body that integrate with the process of maturity in its coordination. Various studies on the development of gross motor skills of children, but in this study aims to determine the child's gross motor development through animal movement games. The research was carried out in PAUD IT Bunayya Pekanbaru in group A with a total of 16 students. This type of qualitative research that researchers apply to this study is to describe the learning outcomes that have been carried out so far by evaluating them through the results of the pretest and posttest. The results revealed that the gross motor development of children through animal movement games in PAUD IT Bunayya Pekanbaru can run well as expected, as the results of the percentage of pretest results of 31.35% have increased in the posttest results of 77.8%. In conclusion, namely the gross motor development of children through animal movement games develop very well